2020
DOI: 10.1097/md.0000000000020089
|View full text |Cite
|
Sign up to set email alerts
|

The financial burden of complications following rectal resection

Abstract: To investigate the costs associated with postoperative complications following rectal resection. Rectal resection is a major surgical procedure that carries a significant risk of complications. The occurrence of complications following surgery has both health and financial consequences. There are very few studies that examine the incidence and severity of complications and their financial implications following rectal resection. We identified 381 consecutive patients who underwent a recta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…From our data, we suggest that hospital costs are primarily driven by major complications rather than the number of complications following DP. This correlation between major complications (CVD grade ≥III) and additional financial burden is consistent with findings from several other studies analysing costs associated with post-abdominal surgery complications ( 12 , 14 , 23 ). However, these studies also found a significant association between the cumulative number of complications and pro-rata cost increases, in contrast to the findings of our study which did not demonstrate a statistically significant link.…”
Section: Discussionsupporting
confidence: 91%
“…From our data, we suggest that hospital costs are primarily driven by major complications rather than the number of complications following DP. This correlation between major complications (CVD grade ≥III) and additional financial burden is consistent with findings from several other studies analysing costs associated with post-abdominal surgery complications ( 12 , 14 , 23 ). However, these studies also found a significant association between the cumulative number of complications and pro-rata cost increases, in contrast to the findings of our study which did not demonstrate a statistically significant link.…”
Section: Discussionsupporting
confidence: 91%
“…We selected 3 types of major abdominal surgery associated with significant perioperative stress response a priori, namely, pancreas, colorectal, and liver resection surgeries. [17][18][19] We included adult patients (≥18 years of age) requiring arterial cannulation for continuous hemodynamic monitoring, with an expected hospital stay of at least 1 postoperative night. Exclusion criteria were an American Society of Anesthesiologists (ASA) physical status score of V, pregnancy or breastfeeding, poorly controlled diabetes mellitus (hemoglobin A1c >9.0% or hemoglobin A1c >75 mmol•mol −1 ), allergy to albumin or dexamethasone, chronic steroid use defined as prednisolone 10 mg per day or equivalent for greater than 1 week in the preceding 3 months, immunosuppressive drugs, and any surgical procedure within the preceding 2 months or expected within the subsequent 30 days.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…This difference is at least in part due to the lack of unanimous commensurate improvement in overall survival with the improvement in complete histopathologic resection rates in pancreaticobiliary cancers. Furthermore, post-operative complications are significant considerations even when curative resections are achieved[ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%